The effect of information booklets on family members' satisfaction with decision making in an Intensive Care Unit of Malaysia - Othman, Hamidah; Subramanian, Pathmawathi; Mohd Ali, Noor Azizah; Hassan, Haszalina; Haque, Mainul (0975-1505, 2016)
Background: To test the effect of information booklets on family members’ satisfaction with decision-making around the care of critically ill patients in an intensive care unit. Design: Quasi-experiment with non-randomized study groups, using a pre and post-test design was used to test the effectiveness of the information booklet. Setting: The study was conducted in a medical center in Malaysia. Subjects: 84 family members of critically ill patients were conveniently assigned to an intervention group and a control group. Intervention: On admission day after consented, completed pre-test questionnaires. The intervention group received the information booklet and will be explained in 20-30 minutes; control group received routine information if any. Day-2: reinforcement on information about 10-20 minutes for intervention group only. Day-3: completion of the post-test questionnaire by both groups. Main outcome measures: The Family Satisfaction–Intensive Care Unit (FS-ICU) and Quality of Communication (QOC) instrument were used to measure families’ satisfaction level. Results: There are significant differences in Family Satisfaction between the intervention and control groups. There was an increase in satisfaction across the pre- and post-test mean values, 54.05 (SD=10. 23) and 71.1 (SD=19.10), respectively; a significant increase in family satisfaction for the intervention group who received the information booklets. Conclusion: The study findings confirm that the information booklets results in a substantial increase in family satisfaction regarding decision-making for patients’ care. Key-words: Decision making, Family satisfaction, Information need, Intensive care unit, Structured Communication.